PENERAPAN MANAJEMEN OPERASIONAL DAN E-FILLING PADA ERA DIGITALISASI DI KPP PRATAMA KOTAMOBAGU - Mokoginta, Sicilya Cahyawati; Mahfudnurnajamuddin, Mahfudnurnajamuddin; Budiandriani, Budiandriani (Universitas Muhammadiyah Tangerang, 2024)
The development of the world of digitalization has triggered increasingly stringent services that make things easier for consumers or the public, so that every service actor or institution must be able to innovate to develop effective ways of serving the publicIn this research we used a research method, namely a qualitative approach. A qualitative approach is a research procedure that provides descriptive data or descriptions that can be built from observations. The research results show the importance of operational management in institutions, because the main activity is the management of all existing resources. Management requires the existence of managers in the organizational structure who have clear authority and responsibility to achieve the stated organizational goals by producing quality goods and/or services at the most effective and efficient production costs and providing a sense of satisfaction to consumers/customers. Processing and organizing the use of resources in production inputs or in updating product advantages or methods of use. The implementation of e-filing should be well socialized to Taxpayers so that Taxpayers can understand matters related to the implementation of e-filing, both in terms of the advantages of implementing the system and its weaknesses as well as the objectives of implementing the e-filing system, so that Taxpayers can be more understand the aims and objectives of implementing the e-filing system.